PENGGUNAAN BLOK GANGLION GASSERI DALAM PENANGANAN NEURALGIA TRIGEMINAL - Yusak Mangara Tua Siahaan, Dimas Prasetyo Chandra (Neurona Majalah Kedokteran Neuro Sains, 2014)
A58YEAROLD FEMALE PATIENT COMPLAINED OF RIGHT FACIAL PAIN SINCE 5 MONTHS PRIOR TO ADMISSION THE PAIN WAS DESCRIBED AS AN ELECTRICAL SHOCK FELT ON RIGHT CHEEK RADIATING TO RIGHT EAR AREA IT WAS EXACERBATED BY BRUSHING TEETH AND CHEWING SCORED 1010 BASED ON NUMERIC PAIN SCALE PHYSICAL AND NEUROLOGICAL EXAMINATIONS WERE NORMAL PATIENT HAD BEEN TREATED WITH CARBAMAZEPINE BUT THE PAIN PERSISTED GASSERIAN GANGLION BLOCK WITH PULSED RADIOFREQUENCY WAS THEN DONE TO THIS PATIENTAFTER THE PROCEDURE THE PAIN SCALE WAS DECREASED TO 310 WITH NO EVIDENCE OF SIDE EFFECT